2003
DOI: 10.1002/ange.200250589
|View full text |Cite
|
Sign up to set email alerts
|

Bromoallenes as Synthetic Equivalents of Allyl Dications: Synthesis of Medium‐Sized Nitrogen Heterocycles through the Cyclization of Bromoallenes in the Presence of a Palladium(0) Catalyst and an Alcohol

Abstract: Eine hoch regio‐ und stereoselektive Cyclisierung zum Aufbau mittelgroßer Stickstoffheterocyclen wurde entwickelt (siehe Schema), die darauf beruht, dass Bromallene in Gegenwart eines Palladium(0)‐Katalysators und eines Alkohols als Äquivalent für ein Allyldikation eingesetzt werden können. Der intramolekulare nucleophile Angriff erfolgt ausschließlich am mittleren Kohlenstoffatom der Allen‐Einheit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
16
0
1
Order By: Relevance
“…These results demonstrate that bromoallene 9 a can act as allyl dication equivalent even in the absence of palladium (0). However, it should be clearly noted that, in the medium-ring formation, [14] the palladium catalyst is essential for successful conversion. For example, treatment of bromoallene 13 with in situ-generated NaOMe in the presence of [PdA C H T U N G T R E N N U N G (PPh 3 ) 4 ] gave the seven-membered ring 14 [14c] in 76 % yield, as a result of the first intramolecular nucleophilic attack on the central carbon atom of the allene moiety followed by the second nucleophilic reaction by methoxide.…”
Section: Formation Of Cyclic Sulfamides Containing a Bicyclo-a C H T mentioning
confidence: 98%
See 2 more Smart Citations
“…These results demonstrate that bromoallene 9 a can act as allyl dication equivalent even in the absence of palladium (0). However, it should be clearly noted that, in the medium-ring formation, [14] the palladium catalyst is essential for successful conversion. For example, treatment of bromoallene 13 with in situ-generated NaOMe in the presence of [PdA C H T U N G T R E N N U N G (PPh 3 ) 4 ] gave the seven-membered ring 14 [14c] in 76 % yield, as a result of the first intramolecular nucleophilic attack on the central carbon atom of the allene moiety followed by the second nucleophilic reaction by methoxide.…”
Section: Formation Of Cyclic Sulfamides Containing a Bicyclo-a C H T mentioning
confidence: 98%
“…[10,11] Currently, reactions of bromoallenes are attracting much interest due to their interesting chemical properties associated with the cumulated double bonds and bromine substituent. [12] However, except for our recent study on ring-forming reactions, [13,14] all the reactions of bromoallenes reported to date are intermolecular reactions. [15,16,17,18] In our previous work, [14] we found that bromoallenes A can act as allyl dication equivalents B in the presence of palladium(0) and alcohol, which are extremely useful for the synthesis of mediumAbstract: A highly regioselective synthesis of bicyclic sulfamides is described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in good agreement with the computational investigation by Prof. Ando. 130) [152][153][154] Medium-sized heterocycles are an extremely important class of compounds, the structural units of which are commonly found within the framework of a variety of natural products. 155) In particular, seven-and eightmembered heterocycles are constituents of a number of compounds with interesting pharmacological properties.…”
Section: )mentioning
confidence: 99%
“…[19] We had reported earlier that the preformed indium propargyl complex 4 [20] yielded fluoroallenyl alcohol 5 when treated with a reactive electrophile, such as aqueous formaldehyde (Scheme 3). [21] Less reactive electrophiles, such as benzaldehyde or imines, produced homopropargyl alcohol or amines.…”
mentioning
confidence: 99%